Negligently inflicted pure economic loss in the case of defective buildings a comparison of South African, English and German law - Hartmann, Wolf (Centre for Law and Society, 2026)
The problem of liability for negligently inflicted pure economic loss appears in many fields of civil liability. Of course this debate does not stop in case of defective buildings after the negligent conduct of a builder or an inspector. The ultimate purchaser of a building or a third party may suffer damage to his person, property or purse through a product that is defective or even through one that is not. He will demand legal redress, and solutions in determining under what conditions it should be successful need to be found. In this context the individual's interest must outweigh the socio-economic utility of damage producing activity, the ensuing liability must be constructed so that it affords adequate protection without stifling beneficial industrial progress.